Case report: Sustained complete remission with ivosidenib in a patient with relapsed, IDH1-mutated acute leukemia - Sahasrabudhe, Kieran; Zhao, Weiqiang; Berg, Miriam; Bhatnagar, Bhavana (Frontiers in Hematology, 2023)
Older patients with acute lymphoblastic leukemia (ALL) have a poor prognosis, with a 5-year overall survival rate of only 10%–20%. This is attributable to patient comorbidities, poor performance status, and high-risk disease biology. The prognosis for patients with relapsed/refractory (R/R) disease remains poor, particularly for patients who are not candidates for therapies targeting CD19 or CD22. Additional treatment options are needed for these patient populations. The patient presented here is a 76-year-old man diagnosed with precursor B-cell ALL with aberrant expression of myeloid markers and lacking significant CD19 or CD22 expression. A 3-year remission was achieved with one cycle of CVP (cyclophosphamide, vincristine, and prednisone) followed by 22 months of maintenance DOMP (dexamethasone, vincristine, methotrexate, and 6-mercaptopurine) prior to relapse. He was then treated with one cycle of salvage CVP, which was complicated by a stroke resulting in hemiparesis. Next-generation sequencing (NGS) was performed on the relapsed bone marrow, which revealed the presence of an R132H mutation in the isocitrate dehydrogenase 1 (IDH1) gene. He was subsequently treated with the IDH1 inhibitor ivosidenib and remained in a second remission for nearly 1 year. IDH1 mutations are present in up to 14% of acute myeloid leukemia (AML) cases but are also seen more rarely in ALL, particularly in cases involving aberrant expression of myeloid markers. Ivosidenib has demonstrated efficacy in patients with IDH1-mutated AML but has not been extensively studied in other hematologic malignancies. This case demonstrates the role of NGS in revealing treatment options in patients with otherwise limited available therapies.